DESAIN WORKSTATION SAUNG KULINER BERDASAR KAJIAN EGO-KULTURAL SUNDA - Edi Setiadi Putra (Universitas Trisakti, 2014)
AbstractOne of the causes of slums in the city of Bandung is the use of untreated tent stalls. The entrepreneurial society does not have the basic culinary culture tent use, because they do not have the sensitivity to maintain it. The tent stalls were originally temporary, has turned into a permanent. Through a review ofethnography, derived the concept of systematic ergonomic working in the kitchen, which is connected with the efficient use of workspace and effective use of a kitchen utensil. In the concept of Sundanese local wisdom, known as the hierarchy level of comfort based on individuals, families and communities,namely 'genah-merenah-tumaninah', characterized by the use of huts 'badak heuay and jogo anjing,' home stage 'jolopong, babancong, sontong', and building 'galudra ngupuk, Jangga wirangga and towering ngapak'. This hierarchy shows the concept of stages in the culinary business Sundanese, according turnover and experience, the tavern, eating houses and restaurants.The design of furniture products in the aesthetic form of huts 'badak heuay and jogo anjing', This is one of the solutions in rediscovering saung that has been lost, because of eroded stall tent of a foreign culture. AbstrakSalah satu penyebab kekumuhan di Kota Bandung adalah penggunaan warung tenda yang tidak terawat. Masyarakat wirausaha kuliner tidak memiliki dasar budaya penggunaan tenda, karena mereka tidak memiliki kepekaan dalam pemeliharaan tenda. Warung tenda yang awalnya bersifat sementara, telah berubah menjadi permanen. Melaluitinjauan etnografi, diperoleh adanya konsep ergonomis tentangsistematika kerja di dapur, yang terhubung dengan pemakaian ruang kerja yang efisien dan penggunaan perkakas dapur yang efektif. Dalam konsep kearifan lokal Sunda, dikenal adanya hirarki kenyamanan berdasarkan tingkatan individu individu, keluarga dan masyarakat, yaitu 'genah-merenah-tumaninah', yang ditandai dengan penggunaan saung 'badak heuay dan jogo anjing', rumah panggung 'jolopong, babancong, sontong', dan gedung 'galudra ngupuk, jangga wirangga dan julang ngapak'. Hirarki ini menunjukkan adanya konsep tahapan dalambisnis kuliner Sunda, sesuai omset dan pengalamannya, yaitu kedai,